Contextualizing Social Studies with Mandar Culture Boosts Primary Learners’ Interest and Achievement - Asriati Asriati; Nursalam Nursalam; Suardi Suardi (FKIP - Universitas Riau, 2026)
Persistent disengagement in primary Social Studies frequently occurs when instruction is weakly connected to pupils’ lived cultural experiences. This study examined the effect of a culturally contextualized pedagogy grounded in Mandar culture on fifth-grade students’ interest and achievement in Social Studies. A quasi-experimental pretest-posttest control group design was implemented in two public primary schools over eight weeks. Data were collected using a Likert-type interest scale, curriculum-aligned achievement tests, classroom observations, and implementation fidelity checklists. Descriptive statistics, assumption tests, independent-samples t tests, and multivariate analysis of variance with alpha set at 0.05 were employed. Compared with the control class, the experimental class showed substantially greater gains in both interest and achievement, and posttest differences between groups were statistically significant. These findings indicate that systematically embedding Mandar cultural elements such as Kalindaqdaq and Sayyang Pattu’du within inquiry-based and collaborative learning meaningfully strengthens student engagement and learning outcomes. The study concludes that integrating local culture into primary Social Studies is an effective strategy for improving both affective and cognitive learning indicators and offers a transferable model for culturally responsive curriculum design.